PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAPHASIL BELAJAR SAINS ANAK USIA 5 – 6 TAHUN DI TAMAN KANAK-KANAK BHINEKA TUNGGAL IKA KECAMATAN BANGKINANG - Anna sholikha sholikha; Wusono Indarto Indarto; Ria Novianti Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is children do not enjoy and became inactive during the science lesson, the lack of attention during studying science, children could not finish the assignments given by the teacher, children became easily tired and bored when studying science, children do not respond well when given a question. The problem formulation in this research is, how is the result of studying science for children with age range from 5-6 years old in Bhineka Tunggal Ika kindergarten before using the contextual learning approach? How is the result of studying science for children with age range from 5-6 years old in Bhineka Tunggal Ika kindergarten after using the contextual learning approach? Is there a significant difference between studying science before and after applying the contextual learning approach in Bhineka Tunggal Ika kindergarten? The aim of this research is to answer the 3 problem formulation above. The number of samples in this researchis 23 kindergarten children of Bineka Tunggal Ika kindergarten of Bangkinang. The method used in this research is the experiment method with one group desaign model. The data analysis is done by statistic percentage technique to differentiate for the result of studying science before anf after using the contextual learning approach on children.  Before using the contextual learning, there were no children categoried “good”. There are 3 children categorized “medium” 13,04% and 20 children categorized “low” 86,96% . After using the contextual learning, some became categorized as “good” is 11 children or 47,83%, and the other 12 children were categorized as “medium” or 52,17%. Based on this research, the information gained shows that the average score of learning science results before given the approach is 20,69. After the teacher gave the approach becomes 36,69. From the calculation of textpoiment it is known that tcount >ttabel (25,199 > 2,704) with a mistake rate of 1%. Therefore, the rejected Ho and the accepted Ha which means there is a significant difference before and after given the approach in the form of contextual learning. Based on the research, it is concluded that after given the contextual learning approach, the result of science learning increases. Keywords:result, studying,contextual learning